An intramolecular C–N cross-coupling of β-enaminones: a simple and efficient way to precursors of some alkaloids of Galipea officinalis - Doušová, Hana; Horák, Radim; Růžičková, Zdeňka; Šimůnek, Petr (Beilstein Journal of Organic Chemistry, 2015)
2-Aroylmethylidene-1,2,3,4-tetrahydroquinolines with the appropriate substituents can be suitable precursors for the synthesis of alkaloids from Galipea officinalis (cuspareine, galipeine, galipinine, angustureine). However, only two, rather low-yielding procedures for their synthesis are described in the literature. We have developed a simple and efficient protocol for an intramolecular, palladium or copper-catalysed amination of both chloro- and bromo-substituted 3-amino-1,5-diphenylpent-2-en-1-ones leading to the above-mentioned tetrahydroquinoline moiety. The methodology is superior to the methods published to date.
Keywords: C–N cross-coupling; copper; enaminone; palladium; tetrahydroquinoline